Rotten to the Cortex: Ceramide-Mediated Lipotoxicity in Diabetic Kidney Disease - Nicholson, Rebekah J.; Pezzolesi, Marcus G.; Summers, Scott A. (Frontiers in Endocrinology, 2021)
Diabetic kidney disease (DKD) is a prevalent and progressive comorbidity of diabetes mellitus that increases one’s risk of developing renal failure. Progress toward development of better DKD therapeutics is limited by an incomplete understanding of forces driving and connecting the various features of DKD, which include renal steatosis, fibrosis, and microvascular dysfunction. Herein we review the literature supporting roles for bioactive ceramides as inducers of local and systemic DKD pathology. In rodent models of DKD, renal ceramides are elevated and genetic and pharmacological ceramide-lowering interventions improve kidney function and ameliorate DKD histopathology. In humans, circulating sphingolipid profiles distinguish human DKD patients from diabetic controls. These studies highlight the potential for ceramide to serve as a central and therapeutically tractable lipid mediator of DKD.